2022
DOI: 10.1002/jcp.30902
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐11/gp130 upregulates MMP‐13 expression and cell migration in OSCC by activating PI3K/Akt and AP‐1 signaling

Abstract: Oral squamous cell carcinoma (OSCC) is an extremely common head and neck cancer with a poor 5‐year survival rate, especially in cases of metastatic disease. Interleukin (IL)‐11 reportedly promotes cell growth and the epithelial–mesenchymal transition process in metastasis. However, the molecular mechanisms of IL‐11 in OSCC metastasis are unclear. This study found that IL‐11 upregulates matrix metalloproteinase 13 (MMP‐13) expression in OSCC via the IL‐11 receptor alpha subunit/glycoprotein 130 receptors that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The role of IL-11 expression was first studied in primary breast cancer, which developed metastasis into the bone [59,60]. IL-11 and its receptor, interleukin-11 receptor α (IL-11Rα) activate STAT3 signaling, which correlates with poor patient prognosis in most human cancers [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL-11 expression was first studied in primary breast cancer, which developed metastasis into the bone [59,60]. IL-11 and its receptor, interleukin-11 receptor α (IL-11Rα) activate STAT3 signaling, which correlates with poor patient prognosis in most human cancers [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Except for the role of ERFE in genomics and chromosomes, our study also identified co-expression of ERFE and IL-11 , a known activator of PI3K-AKT and mTOR signaling pathways [ 43 , 44 ]. In addition, NCAPH expression was also reported to accelerate the tumor progression via PI3K-AKT signaling [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence already exists for FAK hyperactivation in the setting of other neoplasms, such as colorectal cancer [ 47 ]. Notably, IL11 promotes epithelial-to-mesenchymal transition, and has recently been found to act through the activation of MMP-13 (matrix metalloproteinase 13); the same study described a direct correlation between IL11 expression levels and disease stage in oral SCC [ 48 ].…”
Section: Discussionmentioning
confidence: 99%